Is There a (Dis-)Fluency Effect in Learning With Handwritten Instructional Texts? Evidence From Three Studies - Beege, Maik; Krieglstein, Felix; Schneider, Sascha; Nebel, Steve; Rey, Günter Daniel (Frontiers in Education, 2021)
The disfluency effect postulates that intentionally inserted desirable difficulties can have a beneficial effect on learning. Nevertheless, there is an ongoing discussion about the emergence of this effect since studies could not replicate this effect or even found opposite effects. To clarify boundary effects of the disfluency effect and to investigate potential social effects of disfluency operationalized through handwritten material, three studies (N1 = 97; N2 = 102; N3 = 103) were carried out. In all three experiments, instructional texts were manipulated in terms of disfluency (computerized font vs. handwritten font). Learning outcomes and cognitive load were measured in all experiments. Furthermore, metacognitive variables (Experiment 2 and 3) and social presence (Experiment 3) were measured. Results were ambiguous, indicating that element interactivity (complexity or connectedness of information within the learning material) of the learning material is a boundary condition that determines the effects of disfluency. When element interactivity is low, disfluency had a positive effect on learning outcomes and germane processes. When element interactivity increases, disfluency had negative impacts on learning efficiency (Experiment 2 and 3) and extraneous load (Experiment 3). In contrast to common explanations of the disfluency effect, a disfluent font had no metacognitive benefits. Social processes did not influence learning with disfluent material as well.